ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL PENJUMLAHAN DAN PENGURANGAN BILANGAN BERSUSUN - Napfiah, Siti; Zahro, Khorida Masluchiatus (Universitas Insan Budi Utomo, 2022)
This study aims to determine the students' difficulties in solving addition and subtraction problems with composite numbers. This research is a descriptive research with a qualitative approach. The research subjects consisted of three odd semester II students at SD Pakiskembar 2. Students' abilities related to mathematics were indeed different, so there were students who found it difficult when working on math problems. It is suspected that this is because the student has difficulty understanding something abstract. Based on the research, it was found that students experienced difficulties in adding and subtracting compound numbers in the following ways: (1) Students' difficulties in addition and subtraction operations involving zeros, (2) Students did not fully master addition and subtraction procedures, (3) Students difficulty in converting story questions into mathematical form, (4) Students are less careful in reading the questions, (5) Students have not mastered the operation of counting addition by storing, and arithmetic subtraction by borrowing. To anticipate learning difficulties, a learning process is carried out, such as: the application of learning based on the principles of learning mathematics, the concept of learning mathematics, and paying attention to the level of mastery of the material in students.